Incidencia De Los Aspectos Psicosociales En La Deserción De Los Estudiantes Universitarios - Murillo, María Guadalupe Escobar; Alfonso, Arellano Díaz Mario; Armando, Rodríguez Pillajo Lucio; Chunata, Nanci Margarita Inca (European Scientific Journal, ESJ, 2018)
This paper focuses on determining the incidence of the psychosocial aspects of the dropout of students from the School of Marketing at the School of Business Administration of the Higher Polytechnic School in Chimborazo. In this study, the dependent variable include Psychological, Socioeconomic aspects, and its environment. In the dependent variable, the problems of the students, higher education, and social problems were considered. The research was a bibliographic and field research. It was, therefore, developed within the critical and qualitative paradigms. This is attributed to the fact that a dynamic reality was assumed for the diagnosis, analysis, and determination of results. For the collection of data, a survey validated by academic peers was used and executed with a data collection plan for 186 students from first to sixth level (27 teachers and 2 authorities). The data obtained was submitted to a data processing plan, and the analysis and interpretation of the data was later performed. Finally, each psychosocial aspect was submitted to a statistical test which shows that the university desertion has multi-causal origin. It also highlights that the most recurrent have to do with the psychosocial factors that affects the students.